1994
DOI: 10.1111/j.1530-0277.1994.tb00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori, Active Chronic Antral Gastritis, and Gastrointestinal Symptoms in Alcoholics

Abstract: The frequency of Helocobacter pylori (Hp.) infection and active chronic antral gastritis among people with excessive alcohol consumption is not known. A high alcohol intake regularly causes acute gastroduodenitis. In this study, the prevalence of Hp. infection and active chronic antral gastritis in alcoholics compared with nonalcoholic controls was studied. Further, the frequency of gastrointestinal symptoms was registered. Diagnostic methods for Hp. were compared. Twenty-four alcoholics admitted to the hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…Changes in gut microbiota due to the alcohol misuse have been suggested as a key factor in the development of ALD and alcohol-related morbidity and they have been largely explored in several studies [30,31,32,39,40,41,42,43,44,45]. In particular, chronic alcohol overconsumption favors small intestinal malabsorption and modification of colonic bacteria balance, altering also gut microbiota metabolism, as it has been previously demonstrated by Steinar Traae Bjørkhaug and colleagues by using the d -xylose breath test [46].…”
Section: Insight Into the Gut Microbiotamentioning
confidence: 99%
“…Changes in gut microbiota due to the alcohol misuse have been suggested as a key factor in the development of ALD and alcohol-related morbidity and they have been largely explored in several studies [30,31,32,39,40,41,42,43,44,45]. In particular, chronic alcohol overconsumption favors small intestinal malabsorption and modification of colonic bacteria balance, altering also gut microbiota metabolism, as it has been previously demonstrated by Steinar Traae Bjørkhaug and colleagues by using the d -xylose breath test [46].…”
Section: Insight Into the Gut Microbiotamentioning
confidence: 99%
“…Nevertheless, nowadays it is being recognized that Helicobacter pylori infection is a major cause of DU. 14,15 Although the prevalence of H. pylori infection in alcoholic patients is similar to that of control patients, 16 few studies have evaluated the prevalence of this pathogen in chronic alcoholic pancreatitis (CAP). 17,18 Additionally, only one study 17 tried to ascertain whether H. pylori infection is a contributing factor in pathogenesis of DU found in patients with CP.…”
mentioning
confidence: 98%
“…29 The same group of researchers have already demonstrated that the prevalence of Helicobacter pylori infection did not differ between alcoholic patients and controls. 30 This result was confirmed by Buz as in a larger sample study 31 Casafont Morencos and colleagues compared 89 patients with alcoholic cirrhosis and 40 healthy subjects to assess the prevalence of intestinal bacterial overgrowth by H2-glucose breath test. Intestinal bacterial overgrowth was documented approximately in one-third of patients with alcoholic cirrhosis while in none of the healthy subjects.…”
mentioning
confidence: 78%